2017
DOI: 10.1162/jocn_a_01133
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Oscillatory Power and Connectivity in the Human Posterior Cingulate Cortex Supports the Encoding and Retrieval of Episodic Memories

Abstract: Existing data from noninvasive studies have led researchers to posit that the posterior cingulate cortex (PCC) supports mnemonic processes: It exhibits degeneration in memory disorders, and fMRI investigations have demonstrated memory-related activation principally during the retrieval of memory items. Despite these data, the role of the PCC in episodic memory has received only limited treatment using the spatial and temporal precision of intracranial EEG, with previous analyses focused on item retrieval. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 54 publications
5
37
0
Order By: Relevance
“…Positive t--values correspond to an increase in power in ES versus NS conditions. Specifically, we found that hippocampal power decreased in theta band (2--10 Hz) but increased in low gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and high gamma bands (>40Hz) in the ES compared to NS condition across all participants ( Fig. 3b).…”
Section: Figure 3a Shows the Direction Of Power Changes In A Sample mentioning
confidence: 82%
See 2 more Smart Citations
“…Positive t--values correspond to an increase in power in ES versus NS conditions. Specifically, we found that hippocampal power decreased in theta band (2--10 Hz) but increased in low gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and high gamma bands (>40Hz) in the ES compared to NS condition across all participants ( Fig. 3b).…”
Section: Figure 3a Shows the Direction Of Power Changes In A Sample mentioning
confidence: 82%
“…Electrode Localization. Localization of electrodes was performed by pre--surgical planning followed by stereotactic placement of depth electrodes and postoperative fusion of CT images with the pre--operative high--resolution MRI Images (MPRAGE, coronally acquired 1 mm slices) as conducted in our prior studies (40,61). Depth electrodes were labeled using Freesurfer's auto--segmentation software (http://surfer.nmr.mgh.harvard.edu/) (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCN interregional interactions important for memory have been particularly associated with activity synchrony in the theta-frequency band. For instance, human intracranial recordings have shown that HCN regions exhibit neuronal synchrony and phase locking at thetaband frequencies (4-8-Hz) at rest (Foster & Parvizi, 2012), during memory formation (Lega, Jacobs, & Kahana, 2012;Rutishauser, Ross, Mamelak, & Schuman, 2010) and during memory retrieval (Anderson, Rajagovindan, Ghacibeh, Meador, & Ding, 2010;Burke et al, 2014;Foster, Kaveh, Dastjerdi, Miller, & Parvizi, 2013;Lega, Germi, & Rugg, 2017;Steinvorth, Wang, Ulbert, Schomer, & Halgren, 2010;Watrous, Tandon, Conner, Pieters, & Ekstrom, 2013). Likewise, invasive electrical theta-burst stimulation, whereby gamma bursts are applied in a theta cycle ("theta nested gamma"), preferentially induces long-term potentiation in the rodent hippocampus (Larson, Wong, & Lynch, 1986), putatively because this stimulation pattern mimics the endogenous activity of the hippocampus (Buzsaki, 2002).…”
mentioning
confidence: 99%
“…The Default Mode Network (DMN), typically associated with memory system and self-thoughts, has been demonstrated to be affected by age-related cognitive decline, thus presenting reduced FC between the anterior cingulate and posterior cingulate in older individuals (Dennis and Thompson, 2014;Koch et al, 2010). Previous studies have highlighted the pivotal role of cingulate regions in successful memory encoding (Grady et al, 2003;Lee et al, 2016) and retrieval (Lega et al, 2017). Nonetheless, it is not possible to completely evaluate the complexity of human cognitive processes using a single method of analysis.…”
Section: Introductionmentioning
confidence: 99%